`Docile Oriental Women' and Organised Labour: A Case Study of the Indian Garment Manufacturing Industry - Deepita Chakravarty (Indian Journal of Gender Studies 2007; 14; 439, 2007)
This article attempts to understand women's labour market behaviour in the context of export-oriented garment manufacturing in India, particularly women's decision to work and their alleged aversion to unionism. Asian women's submissiveness in the labour market can hardly be the result of `Oriental docility' in every case. We question this assumption by looking at a small sample of 25 women in garment manufacturing firms in Hyderabad, India, and seek other explanations for women's lack of interest in unions, and note the pressures that affect them